Literature for a changing planet - Puchner, Martin 1969- (The Oxford Research Centre in the Humanities/Princeton University Press Lectures in European Culture, 2022)
Why we must learn to tell new stories about our relationship with the earth if we are to avoid climate catastropheReading literature in a time of climate emergency can sometimes feel a bit like fiddling while Rome burns. Yet, at this turning point for the planet, scientists, policymakers, and activists have woken up to the power of stories in the fight against global warming. In Literature for a Changing Planet, Martin Puchner ranges across four thousand years of world literature to draw vital lessons about how we put ourselves on the path of climate change-and how we might change paths before it's too late.From the Epic of Gilgamesh and the West African Epic of Sunjata to the Communist Manifesto, Puchner reveals world literature in a new light-as an archive of environmental exploitation and a product of a way of life responsible for climate change. Literature depends on millennia of intensive agriculture, urbanization, and resource extraction, from the clay of ancient tablets to the silicon of e-readers. Yet literature also offers powerful ways to change attitudes toward the environment. Puchner uncovers the ecological thinking behind the idea of world literature since the early nineteenth century, proposes a new way of reading in a warming world, shows how literature can help us recognize our shared humanity, and discusses the possible futures of storytelling.If we are to avoid environmental disaster, we must learn to tell the story of humans as a species responsible for global warming. Filled with important insights about the fundamental relationship between storytelling and the environment, Literature for a Changing Planet is a clarion call for readers and writers who care about the fate of life on the planet